THE UNITED STATES POLICY IN ISSUING ECONOMIC SANCTION TOWARD NORTH KOREA RELATED TO CHEONAN INCIDENTS - Rafika Nuri (2010)
This thesis try to elaborate the involvement of U.S policy issued economic sanction against North Korea Related to Cheonan Incident. But, this policy believed as a U.S strategy to bring back North Korea into table meeting related to North Korea Nuclear weapon, Six-Party Talk. Six party talks have taken place in the era of President Bush's governance, but can be assessed that the talks have not achieved success because North Korea continues to develop its nuclear program. same as during the reign